Analysis of forefoot bending angle in sprint spikes according to bobsleigh start lap time for development of korean-specific bobsledding shoes - Park, S.; Lee, K.; Kim, D.; Yoo, J.; Jung, J.; Park, K.; Park, S.; Kim, J. (Korean Journal of Sport Biomechanics, 2016)
Objective: The aim of this study was to analyze effects of the toe-spring angle of bobsleigh shoes on start speed lap time to develop Korean-specific bobsled shoes suitable for winter environments and for domestic players on the basis of sports science and optimized biomechanical performance. Method: Seven Korean bobsleigh athletes participated in this study, with three pairs of sprint spikes from three companies (Type A, Type B, Type C). To analyze sprint lap time and forefoot bending angle for each shoe, participants were instructed to drag a sled 15 meters from the start line at a maximum sprint. forefoot bending angle was collected by a high speed camera, and lap time speed was measured. Results: Lap time for type B shoes was 3.52±0.17 sec, type A was 3.55±0.19 sec, and type C was 3.56±0.18 sec. Forefoot bending angles were: angle 1, 6.88±5.55°; angle 2, 9.23±6.38°; angle 3, 15.56±5.39°; angle 4, 9.54±3.85°; angle 5, 9.22±5.08°; angle 6, 7.66±6.44°; and angle 7, 4.30±6.24° (p<.001). Forefoot bending in angle 3 was as follows: type A, 16.47±6.01°; type B, 14.30±4.96°; and type C, 15.90±5.17°. Conclusion: Hard outsoles and midsoles are better than soft type for reduced start lap time when developing a prototype Korean bobsled shoe.